흉부 대동맥류의 외과적 치료 - 안병희; 신성현; 나국주; An, Byeong-Hui; Sin, Seong-Hyeon; Na, Guk-Ju (Taehan Hyungbu Oekwa Hakhoe chi, 1997)
This study represents an attempt to present an analysis of early surgical results in 15 cases of aortic surgery conducted at Chonnam University Hospital between February 1994 to August 1995. The subject, 9 males and 6 females, ranged in age from 32 to 73 years with a mean age of 55.07$±$ 1176 years. The patients were treated for dissecting aortic aneurysm in nine, atherosclerotic aneurysm in 4, and traumatic aortic aneurysm in two. There were 9 cases of median stemotomy, 4 cases of posterolateral thoracotomy, and 2 cases of thoracoabdominal incision. Graft replacement of ascending aorta andfor partial or total aortic arch were performed in 9 patients, descending aorta andfor t oracoabdominal aorta in 3 and total aorta in 1, Two traumatic aortic aneurysms were closed directly. Associate procedures were resuspension of aortic valve in three patients and elephant trunk procedure, coronary reimplantation and aortic valve replacement in one patient. Nine patients underwent operation for ascending aorta andfor aortic arch with retrograde cerebral perfusion during deep hypothermia and circulatory arrest. Perfusion pressure was maintained below 25 mmHg and the mean duration of circulatory arrest was 56.67 $±$ 29.25 minutes. Three patients underwent graft replacement of desending thoracic and thoracoabdominal aorta during deep hypothermia and circulatory arrest. Three patients died of traumatic bile peritonitis, multioragn failure, and rupture of residual dissecting aortic aneurysm by malignant hypertension. Postoperative complications included reoperation for bleeding in 4 patients, temporary confusion in 3, pulmonary complication in 3, and pericardial effusion in . 저자들은 1994년 2월부터 1995년 8월사이에 본 교실에서 흉부대동맥류로 외과적 치료를 받았던 15 례의 임상성적을 분석하여 수술수기 및 수술결과를 향상시키는 계기로 삼고저 한다. 남자가 9례, 여자 가 6례였으며 평균연령은 55.07$±$11.76세였다. 원인질환은 대동맥박리증이 9례, 죽상경화증이 4례, 외 상이 2례이었다. 9례에서 상행 대동맥 및 대동맥궁의 부분 및 완전 치환술을 시행하였으며 3례에서 하행 대동맥 및 흉복부 대동맥치 환술을 시행하였고, 1례에서는 전체 대동백치환술을 시행하였으며, 외 상성 대동맥류 2례에서는 단단문합하였는데 대동맥 박리증 환자에서는 Wheat씨 방법으로 봉합부위를 보강한 후 치환하였다. 9례에서는 정중흉골절개술을, 4례에서는 후외측 흉벽절개술을, 2례에서는 후외 측 흉부절개후 흉복부절개술을 시행하였다. 상행 대동맥 및 대동맥궁을 치환하였던 9례에서는 상대정맥을 통한 역행성 뇌관류를 평균 56.67$±$29.25분 동안 시행하였고 하행 대동맥 및 흉복부 대동맥을 치환하였던 3례에서도 고도의 저체온화를 시행하였는데 술후 항구적인 뇌나 척추 신경장애가 발생한 례는 없었다. 술후 외상성 복담즙에 의한 복막염, 다장기 기능부전, 악성고혈압에 의한 잔여 박리성 동 맥류파열로 3례(20%, 3/15)가 사망하였다. 술후 합병증으로는 출혈에 의한 재수술이 4례, 일시적인 의식장애 3례, 늑막삼출 등의 폐 합병증이 3례, 심낭압진 1례 있었다. 타의료기관에서 관찰중인 1례를 제외한 11례를 추적관찰중인데 사망하거나 만기 합병증을 보인 례는 없었다.